CAM therapies among primary care patients using opioid therapy for chronic pain - Fleming, Sara (BioMed Central, 2007)
BACKGROUND: Complementary and alternative medicine (CAM) is an increasingly common therapy used to treat chronic pain syndromes. However; there is limited information on the utilization and efficacy of CAM therapy in primary care patients receiving long-term opioid therapy. METHOD: A survey of CAM therapy was conducted with a systematic sample of 908 primary care patients receiving opioids as a primary treatment method for chronic pain. Subjects completed a questionnaire designed to assess utilization, efficacy and costs of CAM therapies in this population. RESULTS: Patients were treated for a variety of pain problems including low back pain (38.4%), headaches (9.9%), and knee pain (6.5%); the average duration of pain was 16 years. The median morphine equivalent opioid dose was 41 mg/day, and the mean dose was 92 mg/day. Forty-four percent of the sample reported CAM therapy use in the past 12 months. Therapies utilized included massage therapy (27.3%, n = 248), chiropractic treatment (17.8%, n = 162), acupuncture (7.6%, n = 69), yoga (6.1%, n = 55), herbs and supplements (6.8%, n = 62), and prolotherapy (5.9%, n = 54). CAM utilization was significantly related to age female gender, pain severity income pain diagnosis of neck and upper back pain, and illicit drug use. Medical insurance covered chiropractic treatment (81.8%) and prolotherapy (87.7%), whereas patients primarily paid for other CAM therapies. Over half the sample reported that one or more of the CAM therapies were helpful. CONCLUSION: This study suggests CAM therapy is widely used by patients receiving opioids for chronic pain. Whether opioids can be reduced by introducing such therapies remains to be studied.